STATUS OF FISH FARMING PRACTICES: A CASE STUDY OF SELECTED FISH FARMS IN LAGOS STATE, NIGERIA - OKUNADE, O. A; OLADOSU, G. A.; ADEOGUN, O. A.; AJANI, E. K.; ADEJINMI, J. O.; AKINTAYO, I. A. (Nigerian Journal of Fisheries, 2023)
Fish is essential in human diet, providing the necessary protein components. In aquaculture, fish are produced under controlled environment to support food security. This study assessed the current status of fish farming practices and identified the available resources and culture management practices deployed for fish production in the aquaculture industry in Lagos State. One hundred fish farms were randomly selected from 3 agricultural zones in Lagos, Nigeria; East, West and Far-East. Structured questionnaires were used for data collection, which were analysed using MS Excel tool and descriptive statistics. Men below 50 years of age constitute 53.08% of overall respondents. Use of boreholes as water source was predominant in the East (92.59%) and West (76.67%), while stream/spring was more in the Far-East (75%). Majority of the fish farms operates small-scale; monoculture of clariid catfish is predominant. The stocking densities of ≤ 100/m3 (fingerlings), ≤ 50/m3 (juveniles and adults) and 2,000/m3 (fry) were estimated in grow-out and hatcheries accordingly. Annual average production of fish seeds were ≤ 100,000 while table sized fish (500 – 999g) was prominent per cycle. Mortality was caused in order of importance: water pollution, infections and feed contamination. Therefore, good aquaculture management practices should be adopted to improve production.